The Effect Of Training, Competence, And Leadership On Job Satisfaction With Career Development As An Intervening Variable At Xyz Hospital - Kartika Bunga Fajar; Gurawan Dayona Ismail; Nunung Ayu Sofiati; Mochammad Mukti Ali; Yoyo Sudaryo (Eduvest - Journal of Universal Studies, 2025)
This study aims to examine the influence of training, competence, and leadership on career development, with job satisfaction acting as a mediating variable. The research uses a quantitative approach with a sample of 100 employees, analyzed using multiple linear regression and path analysis. Data were collected through a structured questionnaire, and the classical assumption tests confirmed that the regression model met the requirements of normality, no multicollinearity, and no heteroscedasticity. The results show that training, competence, and leadership have a positive and significant direct effect on both job satisfaction and career development. In addition, job satisfaction also has a significant direct impact on career development, making it a strong mediating variable. The coefficient of determination (R² = 0.648) indicates that 64.8% of the variation in career development is explained by the variables of training, competence, leadership, and job satisfaction. The Sobel test results further confirm that job satisfaction mediates the relationship between the independent variables and career development. These findings suggest that organizations should focus on improving employee training, enhancing competencies, and strengthening leadership practices, as well as maintaining high job satisfaction, to effectively support employees’ career advancement.